Improving English Vocabulary in Kindergarten Students Through One Click English App - Pangestuni, Yoning Eka; Salam, Urai; Maria , Haratua Tiur; Aunurrahman, Aunurrahman; Wicaksono, Luhur (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to overcome the problems in English learning in Perintis II Kindergarten, which faces the limitations of engaging and interactive learning media. Traditional learning methods, such as lectures and flashcards, have not been effective in optimally increasing students' vocabulary mastery. The study developed Android-based learning media to answer this challenge using the Research and Development (R&D) approach. The research process includes product development to evaluate its effectiveness. The results show that the developed application can significantly increase students' vocabulary mastery, with an average score increase of 41.25 points between the pretest and posttest. Teachers responded very positively to the presentation of content in the application. At the same time, parents provided good feedback, although several aspects, such as operations and visuals, still needed improvement. In conclusion, this Android-based learning media effectively supports student learning outcomes while also showing the potential of technology as an innovative learning solution. This application can be an alternative to improve the quality of English learning in Perintis II Kindergarten and contribute to modernizing early childhood education.